In Memoriam: Leonard C. Maximon (1926–2020). (2nd April 2020) - Eskandarian, Ali; Lehman, Donald R.; Parke, William C.; Crow, Michael
Abstract : It is with great sadness that we report the death of our special colleague, Leonard Charles Maximon. Max, as he was called by his friends and colleagues, passed away in his sleep on 4 January 2020, at the age of 94, in Phoenix, Arizona. Leonard Charles Maximon was born in New York in 1926 on New Year's Day. At the end of World War II he was learning to become a U.S. Navy pilot. He received his A.B. degree in Physics from Oberlin College in 1947. He was awarded a Ph.D. degree in Theoretical Physics from Cornell University in 1952 under the supervision of Hans Bethe. The significance of Max's earlier work is captured succinctly by Freeman Dyson in the memorial issue of Physics Today in honor of Hans Bethe (2005). Once, working on a problem in radiative corrections, he was able to solve a particularly troublesome mathematical expression, prompting the praise of a master such as Bethe who asked, "How did you do that?"